1997
DOI: 10.1063/1.473651
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of ruthenium dimers

Abstract: The absorption (scattering depletion) spectrum and resonance Raman spectrum for Ru2 in an argon matrix prepared by the mass-selected ion deposition technique have been obtained. The absorption spectrum in the visible region shows a single broad transition centered at 470 nm. Resonance Raman spectra, obtained by excitation into this band with dye laser radiation, display a single sharp progression with lines at 343.8(26) cm−1, 681.6(32) cm−1, 1017.5(26) cm−1, 1350.2(25)cm−1,and 1678.9(8) cm−1. These data give ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…These values may be compared to our calculated values of 2.265Å, 347.0 cm −1 , and 40.6 kcal · mol −1 , respectively. The experimental estimate of the binding energy is 46.1 kcal · mol −1 30, about 5.5 kcal · mol −1 higher in energy than our calculated value. The theoretical harmonic frequency is in very good agreement with the experimental value of 347.1 cm −1 30.…”
Section: Homonuclear Metal Dimerscontrasting
confidence: 75%
“…These values may be compared to our calculated values of 2.265Å, 347.0 cm −1 , and 40.6 kcal · mol −1 , respectively. The experimental estimate of the binding energy is 46.1 kcal · mol −1 30, about 5.5 kcal · mol −1 higher in energy than our calculated value. The theoretical harmonic frequency is in very good agreement with the experimental value of 347.1 cm −1 30.…”
Section: Homonuclear Metal Dimerscontrasting
confidence: 75%
“…Somewhat later, Moskovits and DiLella reassigned the weaker absorption in between two of the former absorptions to a further transition. For Ru 2 in scattering depletion spectra, a broad transition has been observed at 470 nm …”
Section: Metal Atom Clustersmentioning
confidence: 97%
“…For Ru 2 in scattering depletion spectra, ab road transition has been observeda t 470 nm. [182] Co 2 ,R h 2 :T he earlier work of Ozin and Hanlan [183] assigned severals trong absorptions in the UV (340, 320, 280, 270 nm) and broad weak absorptions in the blue range of the visible spectrum (418 and 442 nm) to Co 2 .T he furtherw ork of Dong et al [184] considered only this latter region, and confirmed a weak unstructured absorption between 425 and 485 nm, with its maximum at 440 nm, and they did not investigate the lower-energy regime. However,D anset and Manceron [185] observed transitions into al arge number of excited electronic states in the absorption spectra, starting from about 500 up to 22 000 cm À1 .B esides the already known broad band with its maximum at around2 2000 cm À1 ,t here is evidence for at least 10 electronic terms, Figure12.…”
Section: Identification Of Excited States In Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Nevertheless, the electronic as well as the atomic structures are far from fully studied and many properties need to be investigated properly to understand their roles in catalytic reactions, though people have made some effort on the geometrical, magnetic, and growth mode of Ru n clusters. 4 For Ru 2 and Ru 3 , the bond lengths and electronic structures were investigated both experimentally 5,6 and theoretically. 4,[7][8][9][10][11][12] In addition to dimer and trimer, other ruthenium clusters have also stimulated intensive research efforts in recent years, especially for Ru 13 and Ru 55 clusters, corresponding to the first and the second geometrical compact shells for both icosahedral ͑I h ͒ and cuboctahedral ͑O h ͒ structures.…”
Section: Introductionmentioning
confidence: 99%